2019
DOI: 10.14202/vetworld.2019.1454-1459
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and species identification of Cryptosporidium spp. in the newborn dairy calves from Muang District, Khon Kaen Province, Thailand

Abstract: Aim:This study aims to determine the prevalence of Cryptosporidium spp. infection and to identify the species of Cryptosporidium spp. in newborn dairy calves between December 2016 and March 2017 in Muang District, Khon Kaen Province, Thailand.Materials and Methods:A total of 200 fecal samples from newborn dairy calves of the ages 1 day up to 28 days were collected and the presence of Cryptosporidium oocysts was examined microscopically using the modified Kinyoun’s acid-fast staining technique. Then, Cryptospor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
1
5
1
Order By: Relevance
“…Only C. bovis and C. ryanae were detected in this study. This finding is consistent with a previous report showing that C. bovis and C. ryanae were mainly found in dairy calves in Khon Kaen, whereas C. andersoni and C. parvum were not detected by nested PCR [ 6 ]. However, there is no agreement with another previous study which revealed that C. parvum was reported in dairy cattle in western Thailand by PCR-RFLP [ 13 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Only C. bovis and C. ryanae were detected in this study. This finding is consistent with a previous report showing that C. bovis and C. ryanae were mainly found in dairy calves in Khon Kaen, whereas C. andersoni and C. parvum were not detected by nested PCR [ 6 ]. However, there is no agreement with another previous study which revealed that C. parvum was reported in dairy cattle in western Thailand by PCR-RFLP [ 13 ].…”
Section: Discussionsupporting
confidence: 93%
“…was 13.51% in cattle aged 1 week–7 years. The prevalence in the present study was lower than that in a previous report (21%) that focused on calves aged only 1–28 days in one district of Khon Kaen province [ 6 ]. However, the prevalence in the present study was close to that of another previous study (15.50%) in Ratchaburi and Kanchanaburi province, Thailand, which studied cattle aged <2 months to more than 4 years [ 13 ].…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…Another study conducted in Nigeria reported that the prevalence of Cryptosporidium was found to be 23.4% (95/406), with an infection rate of 27.4%, 28.1% and 19.9% in cattle less than 6 months, 7-12 months and over 12 months old respectively, using the Kinyoun-acid fast stain method (Ayinmode and Fagbemi 2010). Also, in Thailand, the prevalence of Cryptosporidium oocysts was determined as 51% (102/200) using the Kinyoun--acid fast stain method (Doungmala et al 2019). In addition to these studies, in India, the prevalence of Cryptosporidium spp.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequently used routine techniques for examining stained slides to identify Cryptosporidium spp. are the modified Ziehl–Neelsen ( 54 , 55 ), modified Kinyoun ( 56 , 57 ), and methylene blue safranin ( 58 , 59 ) stains. Additionally, the negative coloring observed with the malachite green technique ( 53 , 60 ) can be used.…”
Section: Diagnostic Methodsmentioning
confidence: 99%